Research on the Application of Color in the Design of Environmental Protection Posters - Xingxing WU , Haiqin OUYANG (Forest Chemicals Review, 1970)
Color can better convey the information through that the author needs to express and achieve better results through various ways, which is not limited by language, text, and pictures. Combined with the basic theory of color and the design principles of environmental protection posters, this paper analyzes the characteristics of color and environmental protection posters and the relationship between them, the advantages of color in poster design and the application of its aesthetic paradigm in environmental protection poster design .Color can bring a stronger resonance to environmental protection posters, beautify the layout structure of public welfare posters, and enhance its expressiveness, communication and influence. By explaining the specific application of color in environmental protection public welfare posters, it guides readers to understand the great value of color in the warning, education and publicity of environmental protection poster design.